2012
DOI: 10.1590/s0100-29452012000400031
|View full text |Cite
|
Sign up to set email alerts
|

Influência do substrato, tamanho de sementes e maturação de frutos na formação de mudas de pitangueira

Abstract: RESUMO-Os experimentos foram realizados na Embrapa ClimaTemperado, e as muda , conduzidas em bandejas de poliestireno expandido, de 72 células, colocadas em casa de vegetação com irrigação manual. O delineamento experimental adotado nos experimentos foi o inteiramente casualizado, em esquema fatorial, utilizando-se de quatro repetições com 12 sementes cada (Experimento 1) e três repetições com 18 sementes cada (Experimento 2). Os tratamentos do Experimento 1 foram o tamanho de semente (média e pequena) e o sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 10 publications
0
13
0
6
Order By: Relevance
“…stigonocarpa seeds present larger primary root emission capacity when compared to large seeds (Pereira et al, 2011). In relation to the root length, medium-sized seeds of Eugenia uniflora L. presented larger growth in relation to small seeds (Antunes et al, 2012).…”
Section: Physiological Qualitymentioning
confidence: 92%
See 1 more Smart Citation
“…stigonocarpa seeds present larger primary root emission capacity when compared to large seeds (Pereira et al, 2011). In relation to the root length, medium-sized seeds of Eugenia uniflora L. presented larger growth in relation to small seeds (Antunes et al, 2012).…”
Section: Physiological Qualitymentioning
confidence: 92%
“…In Dimocarpos longan Lour, the emergence percentage and emergence speed index were not affected by the size of seeds (Oliveira et al, 2005); in Eugenia uniflora L., it was observed that, 90 days after sowing, medium seeds presented a higher emergence percentage (Antunes et al, 2012). This result was similar to that observed in a research with Eugenia uniflora L., in which medium and large seeds resulted in a higher emergence percentage, besides having a longer root length (Klein et al, 2008).…”
Section: The Electrical Conductivity (Ec) Of Medium and Largementioning
confidence: 99%
“…Em seguida, foi realizada uma lavagem das sementes em água corrente por período de 30 min, com a finalidade de retirar os resíduos de polpa e cal virgem remanescente (ANTUNES et al, 2012). Após a lavagem as sementes foram colocadas sob papel toalha, à sombra, em temperatura ambiente (± 25 °C) para retirada do excesso de umidade das sementes.…”
Section: Methodsunclassified
“…A maioria dos pomares de pitangueira é formada a partir de mudas resultantes da propagação seminífera, ou seja, através de semente (ANTUNES et al, 2012). Apesar disso, existe carência de conhecimentos básicos sobre a germinação de sementes de pitangueira.…”
Section: Introductionunclassified
See 1 more Smart Citation